2012
DOI: 10.1109/jstsp.2012.2215306
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Subjects and Environment on Audiovisual Subjective Tests: An International Study

Abstract: International audienceTraditionally, audio quality and video quality are evaluated separately in subjective tests. Best practices within the quality assessment community were developed before many modern mobile audiovisual devices and services came into use, such as internet video, smart phones, tablets and connected televisions. These devices and services raise unique questions that require jointly evaluating both the audio and the video within a subjective test. However, audiovisual subjective testing is a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 28 publications
1
57
0
Order By: Relevance
“…This conclusion is in line with the observations made by psychologists [2] [17]. The above assertion is also in line with the observation made by other researchers working in a similar discipline [57]. This conclusion is also consistent with the recently issued ITU-T Recommendation P.800.2 [32] regarding the interpretation of MOS results.…”
Section: Relative Properties Of Scoressupporting
confidence: 92%
See 1 more Smart Citation
“…This conclusion is in line with the observations made by psychologists [2] [17]. The above assertion is also in line with the observation made by other researchers working in a similar discipline [57]. This conclusion is also consistent with the recently issued ITU-T Recommendation P.800.2 [32] regarding the interpretation of MOS results.…”
Section: Relative Properties Of Scoressupporting
confidence: 92%
“…The observation that the effect of the labels on the nonlinearity of the scale is much smaller than initially assumed is in line with the reports from the international multi-laboratory experiments. Despite a great likelihood of nonlinear bias in such tests, for example due to translation issues, the data obtained for the same stimuli from various laboratories are typically collinearly related [57] [58]. Interestingly, in one of the pioneering studies from the field of speech quality assessment, some researchers used the label "unsatisfactory" instead of the standard term "bad."…”
Section: Labels and Non-linearity Issuesmentioning
confidence: 99%
“…There were 26 male and 3 female participants working at the Department of Computer Science, Electrical and Space Engineering at Luleå University of Technology, Sweden. The choice of the number of participants for the subjective study was based on studies presented in the state-of-theart [33], [9], [41]. For example, Wu et al [41] considered sixteen users for subjective and objective tests.…”
Section: Results Analysis Based On User Studies/subjective Tests Methodsmentioning
confidence: 99%
“…For instance, in the context of subjective quality assessment, Ref. [14] recommends a minimum of 15 subjects while the authors in [15] suggested using at least 24 subjects for audiovisual quality measurement. Because the sampling distribution of mean is directly or indirectly used in computing the test statistics such as t, F etc., there are no requirements of normality (or any other distribution) on the data to be analyzed.…”
Section: B the Case Of Anova And F -Testmentioning
confidence: 99%